Impact of indoor air polluti on by microscopic fungi on population health (Environment & Health, 2023)
Objective: to determine the impact of mycomycete contamination of air in residential and public buildings on human health.Materials and methods of research: Microbiological and mycological analysis of indoor air was studied by conventional methods. A questionnaire was developed and a survey of residents of the surveyed housing was conducted. Statistical processing of the obtained results, reliability of the obtained data, calculations were performed with using the STATISTICA 8 program and Microsoft Excel program.Results: As a result of field studies of houses’ residential premises of different construction periods and a questionnaire survey of residents, the features of microbiological contamination of the air environment were established. It is shown that in houses commissioned more than twenty years before, air pollution by spores of microscopic fungi was almost twice as high as in the buildings’ air of later development. At the same time, the role of maintenance’s state of the living space, that is, the economic behavior of the residents themselves, was also revealed. Based on the questionnaire, informational characteristics of the relationship between the health status of residential premises residents and objective indicators of the microclimate on the basis of biodamages were developed. The reliability of the obtained data is p
Keywords: air; premises; mycological contamination; microscopic fungi; health